Effects of covering structures and gibberellic acid in promoting seed germination of Urochloa - Salazar, Daniel E.; Santos-M, Luis Guillermo; Guzzon, Filippo; Wenzl, Peter (Springer, 2025)
Forage grass species of the genus Urochloa play a crucial role in tropical and subtropical ecosystems, particularly in Latin America, where they are important for livestock production due to their adaptability and productivity. Despite their economic importance, there are no definitive conclusions about dormancy-breaking methods in this genus. This study examined 34 seed lots of U. brizantha, U. ruziziensis, U. decumbens, and U. humidicola, conserved at the International Center for Tropical Agriculture (CIAT) genebank for different periods (from one to 22 years in storage). Seeds of all four species showed high viability for up to 21–22 years of long-term storage, estimated by tetrazolium tests. Additionally, removal of seed covering structures significantly promoted final germination, highlighting the efficacy of this simple method to break seed dormancy in U. brizantha, U. ruziziensis, and U. decumbens, with germination results not statistically different from tetrazolium tests for these three species. However, this method was less efficient in achieving high germination percentages for seeds of U. humidicola, and further research is needed to identify efficient dormancy breaking methods for this species. Finally, this study found that gibberellic acid treatments did not promote seed germination in any of the four evaluated species.